2013
DOI: 10.1128/jvi.01289-13
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Parainfluenza Virus 5 Mutants Expressing Hemagglutinin from H5N1 Influenza A Virus in Mice

Abstract: Parainfluenza virus 5 (PIV5) is a promising viral vector for vaccine development. PIV5 is safe, stable, efficacious, cost-effective to produce and, most interestingly, it overcomes preexisting antivector immunity. We have recently reported that PIV5 expressing the hemagglutinin (HA) from highly pathogenic avian influenza (HPAI) virus H5N1 (PIV5-H5) provides sterilizing immunity against lethal doses of HPAI H5N1 infection in mice. It is thought that induction of apoptosis can lead to enhanced antigen presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…We also observed that rMuV⌬SH induced slightly higher total antibody titers than those induced by rMuV, and rMuV⌬SH⌬V induced higher antibody titers than those induced by rMuV⌬V, suggesting that deletion of SH leads to better antigen presentation. Similar results have been reported for a closely related virus, parainfluenza virus 5 (PIV5), in which PIV5 lacking SH is more immunogenic than PIV5 (88). The mouse models have been widely used to test vaccine efficacy for various human viruses (89)(90)(91)(92).…”
Section: Discussionsupporting
confidence: 61%
“…We also observed that rMuV⌬SH induced slightly higher total antibody titers than those induced by rMuV, and rMuV⌬SH⌬V induced higher antibody titers than those induced by rMuV⌬V, suggesting that deletion of SH leads to better antigen presentation. Similar results have been reported for a closely related virus, parainfluenza virus 5 (PIV5), in which PIV5 lacking SH is more immunogenic than PIV5 (88). The mouse models have been widely used to test vaccine efficacy for various human viruses (89)(90)(91)(92).…”
Section: Discussionsupporting
confidence: 61%
“…Two recombinant PIV5 viruses containing the NA gene between the HN and L genes, ZL108 (rPIV5-H1N1-N1-HN/L) and ZL116 (rPIV5-H5N1-N1-HN/L), were generated as previously described (24)(25)(26)(27)(28). Plasmid pZL108 or pZL116 and three helper plasmids, pPIV5-NP, pPIV5-P, and pPIV5-L, encoding the NP, P, and L proteins, respectively, were cotransfected into BSR-T7 cells, and after 72 h of incubation at 37°C, the media were harvested and cell debris was pelleted by low-speed centrifugation (3,000 rpm for 10 min).…”
Section: Methodsmentioning
confidence: 99%
“…PIV5 titers were determined by a plaque assay on Vero cells as previously reported (24,26). Briefly, cells were incubated with serial dilutions of the virus for 2 h, the virus was removed, and cells were overlaid with 1:1 low-melting-point agarose and DMEM with 2% FBS plus antibiotic-antimycotic and incubated at 37°C for 5 to 6 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PIV5 can infect humans and animals without causing any known symptoms or diseases (3,4). It has been used as a vector for vaccine development (5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%